2021
DOI: 10.1155/2021/6637200
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Acoustic Emission and Resistivity Response of Sandstone under Constant Amplitude Cyclic Loading

Abstract: A lot of engineering practice shows that, during the construction and operation of rock mass projects, in addition to the static load, the rock is more subjected to cyclic load. Constant amplitude cyclic load is one of the simpler cyclic loading methods. The damage of rocks gradually accumulates under the action of periodic cyclic load, and finally, fatigue damage occurs, which affects the stability of the project. Therefore, it is necessary to study the mechanical properties of the rock under the action of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The resistivity variation with stress during the loading process is shown in Figure 13(a) and (b), while the resistivity variation during complete loading and unloading of the specimen is shown in Figure 13(c) and (d). The specific relationship between resistivity and stress variation is as follows [27,28] :…”
Section: The Characteristics Of Resistivity Variation During the Cycl...mentioning
confidence: 99%
“…The resistivity variation with stress during the loading process is shown in Figure 13(a) and (b), while the resistivity variation during complete loading and unloading of the specimen is shown in Figure 13(c) and (d). The specific relationship between resistivity and stress variation is as follows [27,28] :…”
Section: The Characteristics Of Resistivity Variation During the Cycl...mentioning
confidence: 99%
“…On the other hand, cyclic loading significantly affects the physical properties and mechanical response of granite. Recent findings indicated that the fatigue failure of rocks can be categorized into three distinct stages: the initial deformation stage, the constant deformation stage, and the accelerated deformation stage, as detailed in the studies of Wang et al [23,24]. Extensive research has been conducted to investigate the impact of cyclic loading on the fracture toughness of rocks [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…J. Guo studied the acoustic emission signal characteristics of igneous rocks with different water content under cyclic loading and unloading [8]. K. Wang studied the acoustic emission parameters and resistivity characteristics of sandstone with different saturation under constant amplitude cyclic load [9]. J. Wu studied the acoustic emission signal characteristics of concrete cube specimens having different sizes under cyclic loading and unloading [10].…”
Section: Introductionmentioning
confidence: 99%